The refugee child equipped :an exploration of the English language acquisition through the mantle of the expert drama approach to build the language repertoire of children of Bienvenu Shelter - Bambo, Natasha (My University, 2019)
This research was conducted at Bienvenu, a shelter in Johannesburg for migrants and displaced women and children. The group of participants were four 6-8 year old refugee children who resided at Bienvenu and benefitted from the support offered. The children came from non-English speaking nations but had a grasp of English. This research addressed the further development of the children’s English through the use of a Drama in Education approach (DIE) called Mantle of the Expert (MOE). The aim was for the children to develop their English skills as well as attend to their homework through MOE. How effective this approach was in achieving this aim was explored. Nine important MOE elements were identified and unpacked with reference to the experience of applying this approach. The research methodology was Action Research. It is characterised by operating in cycles where action is taken then reflection upon the action happens. The reflection contributes to potential change in future action, which then leads into another cycle of action and reflection. The MOE elements were found to be beneficial for language skills development. The application and use of the elements improved the more they were used and ‘tested’ but also as a result of developing an understanding about the interests and needs of the children. The value of the outcomes is that of approaching DIE work with a greater awareness about children’s needs, their strengths and weaknesses and formulating learning experiences that they can find memorable and engaging.
This research was submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master’s in Applied Drama Johannesburg 2019